The Impact of Performance Expectancy, Effort Expectancy, Habit, and Price Value on The Behavioral Intention of Tokopedia Users in Jakarta - Odelia Odelia; Tommy Setiawan Ruslim (International Journal of Application on Economics and Business, 2023)
The development of increasingly advanced technology now has a big impact and greatly affects human activities that make human life easier, one of which is the online shopping application at Tokopedia. The focus on this study is to determine the effect of performance expectations, effort expectations, habit, and price value ​​on the behavioral intention of the Tokopedia application in Jakarta. This study used 200 samples with purposive sampling method, namely those using the Tokopedia application in Jakarta with ages above 20 years which was carried out in the form of google form. The results is all variables have a positive effect on the behavioral intention of Tokopedia users except for the performance expectation variable which not have a significant effect on the behavioral intention of Tokopedia users. In this study, it was found that the variable that had the most influence on behavioral intentions was habit.